An iTEP-salinomycin nanoparticle that specifically and effectively inhibits metastases of 4T1 orthotopic breast tumors. (July 2016) - Zhao, Peng; Xia, Guiquan; Dong, Shuyun; Jiang, Zhaong-Xing; Chen, Mingnan
Abstract: Cancer stem cell (CSC) inhibitors are a new category of investigational drugs to treat metastasis. Salinomycin (Sali) is one of most studied CSC inhibitors and has reached clinical tests. Several drug carriers have been developed to improve efficacy of Sali. However, Sali has not been shown to inhibit metastasis from orthotopic tumors, the gold standard for metastasis. To fill this gap, we developed an immune-tolerant, elastin-like polypeptide (iTEP)-based nanoparticle (iTEP-Sali-ABA NP) that released 4-(aminomethyl)benzaldehyde-modified Sali (Sali-ABA) under acidic conditions. We found that the NP increased the area under the curve (AUC) of Sali-ABA by 30-fold and the tumor accumulation by 3.4-fold. Furthermore, no metastasis was detected in any of the mice given the NP. However, all the mice died of primary tumor burdens. To overcome primary tumor growth and improve the overall survival, we applied a combination therapy consisting of the iTEP-Sali-ABA NP and iTEP NP-delivered paclitaxel. This therapy effectively retarded primary tumor growth, and most importantly, improved the overall survival. In conclusion, delivery of Sali-ABA by the NP, alone or in combination with paclitaxel, was more effective than free Sali-ABA in decreasing metastasis and increasing survival. This iTEP-Sali-ABA NP represents a novel and clinically promising therapy to combat metastasis.